The Position and Role of the Village Council in Making Village Regulations in Dawuhan Kulon Village, Banyumas - Hartini, Sri; Budiyono, Budiyono; Kunarti, Siti; Haryanto, Tenang; Kupita, Weda (MIH FH UNSOED, 2024)
Village Council (BPD) plays an important role in the formation of village regulation (Perdes). Strengthening the role of BPD in legislation is an effort to improve the quality of village regulation products. This is outlined in Article 61 Village Law, BPD is an institution that embodies democracy in the administration of village governance that functions to accommodate and channel community aspirations, carry out the task of supervising the performance of the Village Head, and together with the Village Head, discuss and agree on the draft village regulation in Dawuhan Kulon Village during 2020-2023 was 24 Perdes’s. One person was purely an initiative for BPD. This research shows that the Dawuhan Kulon BPD, in its role in the initiative to create village regulations, has not been optimal, as seen from the number of Perdes produced. BPD's position in carrying out aspirations is carried out through community activities. BPD places itself as an extension of the village community. Activities are carried out to socialize information on village development, accommodate community aspirations for village regulations, and agree with the Village Head. Recommendations from this research are formulated such that the community is aware that village regulation is a legal product for the benefit of the community; therefore, the community also needs to be involved. The BPD should socialize with its citizens through Rukun Tetangga meetings if there will be discussions and the creation of Perdes.